The effects of exposure to literary texts on reading comprehension and vocabulary retention: literature-majors vs translation-majors - Shirin Rahimi Kazerooni (Penerbit Universiti Kebangsaan Malaysia, 2013)
This study attempts to examine the impact of reading literary texts on vocabulary retention of learners of English as a foreign language (EFL). Some Iranian undergraduate students (n=140) randomly selected from among senior students of English literature and English translation participated in this investigation. The results of one-way ANOVAs brought to light the fact that exposure to a plethora of literary material does not necessarily bring about any significant gain in literature majors’ comprehension of literary or nonliterary texts. Even so, as reading literary texts improves the retention of vocabulary items, a literature-based methodology for teaching vocabulary is recommended